Ternary insulation coated metal magnetic powder core and preparation method and application thereof
By performing particle size grading and ternary insulation coating on metal magnetic powder, the problem of large loss of metal magnetic powder core at high frequency is solved, the effects of low loss, high magnetic permeability and high magnetic induction strength are achieved, and the insulation layer is improved The heat resistance of the company has broadened the application field.
Patent Information
- Application Number
- CN202310805570.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-03
AI Technical Summary
The existing metal magnetic powder cores have large losses at high frequencies, which are difficult to meet the requirements of low loss, high magnetic permeability and high magnetic induction strength. At the same time, the insulation layer has poor heat resistance, which limits its application fields.
The preparation method of metal magnetic powder core coated with ternary insulation is adopted. By grading the metal magnetic powder in particle size, mixing it with inorganic insulating powder, organic insulating agent and adhesive, and after pressing and heat treatment, it forms low loss, high magnetic permeability and high Magnetic powder core with magnetic induction strength.
It effectively reduces eddy current loss, improves the heat resistance and current resistance of the insulating layer, broadens the application field, and is simple in process and low in cost, suitable for large-scale industrial production.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic materials and relates to a metal magnetic powder core, in particular to a ternary insulation-coated metal magnetic powder core and a preparation method and application thereof. Background Art
[0002] Magnetic powder core refers to a composite soft magnetic material made by mixing magnetic metal powder with an insulating agent and an adhesive and then pressing it. Insulation coating is a key step in the preparation of metal soft magnetic composite materials. Generally, the insulating layer is required to be thin and uniform enough, have a high bonding strength with the matrix, and have high resistivity and thermal stability. The new generation of electronic devices has the characteristics of large current and high frequency, which makes the loss of magnetic powder core increase exponentially, limiting its application areas. Normally, hysteresis loss is proportional to frequency, and eddy current loss is proportional to the square of frequency. Therefore, when the material is used for high frequency, it is crucial to reduce the eddy current loss in the material. Those skilled in the art are in urgent need of developing a metal magnetic powder core with strong current resistance and low loss.
[0003] CN 112185640A discloses a method for coating a magnetic powder core with sodium silicate, wherein alcohol ether phosphate is used as a dispersant for sodium silicate, lignin sulfonate is used as a dispersant for metal magnetic powder, the dispersed sodium silicate solution is mixed with the dispersed metal magnetic powder for coating, after drying, an adhesive and a lubricant are added, and then molded, and finally high-temperature annealing is performed to obtain a sodium silicate-coated magnetic powder core. The magnetic core loss prepared by the invention is 242-267mW / cm 3 (50kHz 100mT), the DC bias performance is 29.5%-36.4%, and the DC bias is low. Therefore, the application field of this material is small and cannot meet the requirements of low material loss and high DC superposition characteristics.
[0004] CN 1224899A discloses a composite magnetic body, a method for producing the same and Fe-Al-Si soft magnetic alloy powder used therein. Organic substances such as epoxy resin and phenolic resin are used as insulating substances between metal magnetic particles to coat the soft magnetic composite material. The composite material has the characteristics of strong bonding ability with magnetic powder, but lacks effective modification or even conversion between insulating substances, and the heat resistance of the insulating layer is poor.
[0005] It can be seen that how to provide a metal magnetic powder core and a preparation method thereof to meet the requirements of low material loss, high magnetic permeability and high magnetic induction intensity, while improving the heat resistance of the insulating layer, enhancing its current resistance and broadening the application field has become an urgent problem that technical personnel in this field need to solve. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a ternary insulation coated metal magnetic powder core and a preparation method and application thereof. The ternary insulation coated metal magnetic powder core is obtained by coating and granulating the surface of the metal magnetic powder particles with a material with strong insulation and adhesion, and pressing and heat treating the ternary insulation coated metal magnetic powder core, which meets the requirements of low material loss, high magnetic permeability and high magnetic induction intensity, while improving the heat resistance of the insulation layer, enhancing its current resistance and broadening the application field.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a ternary insulation-coated metal magnetic powder core, the preparation method comprising the following steps:
[0009] (1) Classifying the particle size of metal magnetic powder;
[0010] (2) mixing metal magnetic powder and inorganic insulating powder to obtain a first magnetic powder;
[0011] (3) mixing the first magnetic powder, the organic insulating agent and the adhesive, and drying to obtain the second magnetic powder;
[0012] (4) mixing the second magnetic powder and the lubricant, and pressing the mixture into a ring to obtain a metal magnetic ring;
[0013] (5) The metal magnetic ring is heat treated to obtain a metal magnetic powder core coated with a ternary insulation.
[0014] Wherein, the metal magnetic powder in step (1) includes iron silicon alloy magnetic powder and / or iron silicon aluminum alloy magnetic powder, and the particle size of the metal magnetic powder is 5-100μm, for example, it can be 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm or 100μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0015] The present invention targets iron-based alloy magnetic powder of specific particle size, and respectively uses inorganic insulating powder, organic insulating agent and adhesive to insulate and coat it, and then presses it into a ring, and eliminates the internal stress generated in the pressing process through heat treatment, so as to finally obtain a metal magnetic powder core with low loss, high superposition and high quality factor; wherein, the insulating coating increases the resistivity of the soft magnetic composite material, thereby effectively reducing the eddy current loss between particles, and broadening the application field of the soft magnetic composite material.
[0016] In addition, the preparation method provided by the present invention has a simple process flow, convenient operation, low cost, high production efficiency, and the method is green and environmentally friendly and suitable for large-scale industrial production.
[0017] Preferably, the particle size classification standards in step (1) include: D50=5-20 μm, D50=20-35 μm and D50=35-75 μm.
[0018] Wherein, D50=5-20μm, for example, D50=5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm; D50=20-35μm, for example, D50=20μm, 21μm, 22μm, 23μm, 24μm, 25μm , 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm or 35μm; D50=35-75μm, for example, D50=35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm or 75μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the inorganic insulating powder in step (2) comprises any one of kaolin, glass powder or silica, or a combination of at least two of them. Typical but non-limiting combinations include a combination of kaolin and glass powder, a combination of glass powder and silica, a combination of kaolin and silica, or a combination of kaolin, glass powder and silica.
[0020] Preferably, the average particle size of the kaolin is 200-1000 mesh, for example, it can be 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh, 500 mesh, 550 mesh, 600 mesh, 650 mesh, 700 mesh, 750 mesh, 800 mesh, 850 mesh, 900 mesh, 950 mesh or 1000 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the average particle size of the glass powder is 200-1000 mesh, for example, it can be 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh, 500 mesh, 550 mesh, 600 mesh, 650 mesh, 700 mesh, 750 mesh, 800 mesh, 850 mesh, 900 mesh, 950 mesh or 1000 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the average particle size of the silicon dioxide is 1000-2000 mesh, for example, it can be 1000 mesh, 1100 mesh, 1200 mesh, 1300 mesh, 1400 mesh, 1500 mesh, 1600 mesh, 1700 mesh, 1800 mesh, 1900 mesh or 2000 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, the proportion of the inorganic insulating powder in the first magnetic powder in step (2) is 0.5-5wt%, for example, it can be 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5.0wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, the type and particle size of the inorganic insulating powder in step (2) are compatible with the particle size classification of the metal magnetic powder, specifically including: when the inorganic insulating powder is kaolin and / or glass powder with an average particle size of 200-400 mesh, the metal magnetic powder with a mixed particle size of D50=35-75μm; when the inorganic insulating powder is kaolin and / or glass powder with an average particle size of 400-1000 mesh, the metal magnetic powder with a mixed particle size of D50=20-35μm; when the inorganic insulating powder is silica with an average particle size of 1000-2000 mesh, the metal magnetic powder with a mixed particle size of D50=5-20μm.
[0025] The present invention introduces inorganic insulating powder compatible with the surface of metal magnetic powder of specific particle size classification, and then introduces high-temperature resistant organic insulating agent and adhesive to form a ternary coating system. The magnetic powder is directly heat-treated after being pressed and formed, which effectively avoids decomposition and crystallization of the inner layer material at high temperature annealing temperature.
[0026] Preferably, the mixing method in step (3) includes: firstly adding an organic insulating agent to the first magnetic powder for insulation treatment, stirring evenly, and then adding an adhesive for reinforcement treatment.
[0027] Preferably, the organic insulating agent comprises silane, and the type of the silane comprises any one of KH-550, KH-621, KH-631, DL-602 or DL-171, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of KH-550 and KH-621, a combination of KH-621 and KH-631, a combination of KH-631 and DL-602, a combination of DL-602 and DL-171, a combination of KH-550, KH-621 and KH-631, a combination of KH-621, KH-631 and DL-602, or a combination of KH-631, DL-602 and DL-171.
[0028] Preferably, the proportion of the organic insulating agent in the second magnetic powder is 0.5-1.5wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the adhesive comprises a silicone resin, and the type of the silicone resin comprises any one of methyl silicone resin KR-251, polyester resin modified silicone KR-5235, alkyl silicone resin JM10 or methyl phenyl silicone resin REN60, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of methyl silicone resin KR-251 and polyester resin modified silicone KR-5235, a combination of polyester resin modified silicone KR-5235 and alkyl silicone resin JM10, a combination of alkyl silicone resin JM10 and methyl phenyl silicone resin REN60, a combination of methyl silicone resin KR-251, polyester resin modified silicone KR-5235 and alkyl silicone resin JM10, and a combination of polyester resin modified silicone KR-5235, alkyl silicone resin JM10 and methyl phenyl silicone resin REN60.
[0030] Preferably, the proportion of the adhesive in the second magnetic powder is 1.0-5.5wt%, for example, it can be 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt% or 5.5wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the organic insulating agent and the adhesive are separately diluted before being added.
[0032] Preferably, the organic insulating agent uses anhydrous ethanol as a diluent, and the volume ratio of the diluent to the organic insulating agent is (1.5-2.5):1, for example, it can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the adhesive uses acetone as a diluent, and the volume ratio of the diluent to the adhesive is (1.5-2.5):1, for example, it can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the lubricant in step (4) comprises zinc stearate, and the proportion of the lubricant in the metal magnetic ring is 0.3-0.4wt%, for example, it can be 0.3wt%, 0.31wt%, 0.32wt%, 0.33wt%, 0.34wt%, 0.35wt%, 0.36wt%, 0.37wt%, 0.38wt%, 0.39wt% or 0.4wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the temperature for pressing into rings in step (4) is 20-30°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the pressure for pressing into a ring in step (4) is 1500-2500 MPa, for example, it can be 1500 MPa, 1600 MPa, 1700 MPa, 1800 MPa, 1900 MPa, 2000 MPa, 2100 MPa, 2200 MPa, 2300 MPa, 2400 MPa or 2500 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the specifications of the metal magnetic ring in step (4) are (26-28) mm OD×(14-16) mm ID×(10-12) mm tall, and OD, ID and tall respectively refer to the outer diameter, inner diameter and height of the metal magnetic ring.
[0038] The outer diameter OD of the metal magnetic ring is 26-28 mm, for example, it can be 26 mm, 26.2 mm, 26.4 mm, 26.6 mm, 26.8 mm, 27 mm, 27.2 mm, 27.4 mm, 27.6 mm, 27.8 mm or 28 mm; the inner diameter ID of the metal magnetic ring is 14-16 mm, for example, it can be 14 mm, 14.2 mm, 14.4 mm, 14.6 mm, 14.8 mm, 15 mm, 15.2mm, 15.4mm, 15.6mm, 15.8mm or 16mm; the height of the metal magnetic ring is 10-12mm, for example, it can be 10mm, 10.2mm, 10.4mm, 10.6mm, 10.8mm, 11mm, 11.2mm, 11.4mm, 11.6mm, 11.8mm or 12mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] Preferably, the heat treatment in step (5) is performed in a nitrogen and / or inert gas atmosphere, and the inert gas includes helium and / or argon.
[0040] Preferably, the temperature of the heat treatment in step (5) is 700-850°C, for example, it can be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the heat treatment time in step (5) is 30-40 min, for example, it can be 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] As a preferred technical solution of the first aspect of the present invention, the preparation method comprises the following steps:
[0043] (1) performing particle size classification on metal magnetic powder with a particle size of 5-100 μm, wherein the particle size classification standards include: D50=5-20 μm, D50=20-35 μm and D50=35-75 μm, and the metal magnetic powder includes iron silicon alloy magnetic powder and / or iron silicon aluminum alloy magnetic powder;
[0044] (2) mixing metal magnetic powder and inorganic insulating powder to obtain a first magnetic powder; the inorganic insulating powder comprises any one of kaolin, glass powder or silicon dioxide or a combination of at least two thereof, and the average particle size of the kaolin and glass powder is independently 200-1000 mesh, and the average particle size of the silicon dioxide is 1000-2000 mesh; the proportion of the inorganic insulating powder in the first magnetic powder is 0.5-5wt%, and the type and particle size of the inorganic insulating powder are suitable for the particle size classification of the metal magnetic powder. The method comprises: when the inorganic insulating powder is kaolin and / or glass powder with an average particle size of 200-400 mesh, the metal magnetic powder with a particle size of D50=35-75 μm is mixed; when the inorganic insulating powder is kaolin and / or glass powder with an average particle size of 400-1000 mesh, the metal magnetic powder with a particle size of D50=20-35 μm is mixed; when the inorganic insulating powder is silicon dioxide with an average particle size of 1000-2000 mesh, the metal magnetic powder with a particle size of D50=5-20 μm is mixed;
[0045] (3) firstly adding an organic insulating agent to the first magnetic powder for insulation treatment, stirring evenly, then adding an adhesive for reinforcement treatment, and drying to obtain a second magnetic powder; the organic insulating agent comprises silane, which accounts for 0.5-1.5wt% of the second magnetic powder, and the type of the silane comprises any one of KH-550, KH-621, KH-631, DL-602 or DL-171 or a combination of at least two; the adhesive comprises an organic silicone resin, which accounts for 1.0-5.5wt% of the second magnetic powder, and the organic silicone resin comprises an organic silicone resin. The type of resin includes any one of methyl silicone resin KR-251, polyester resin modified silicone KR-5235, alkyl silicone resin JM10 or methyl phenyl silicone resin REN60, or a combination of at least two thereof; the organic insulating agent and the adhesive are independently diluted before being added, and the organic insulating agent uses anhydrous ethanol as a diluent, and the volume ratio of anhydrous ethanol to the organic insulating agent is (1.5-2.5):1; the adhesive uses acetone as a diluent, and the volume ratio of acetone to the adhesive is (1.5-2.5):1;
[0046] (4) mixing the second magnetic powder and zinc stearate, pressing into a ring at 20-30° C. and 1500-2500 MPa to obtain a metal magnetic ring; the ratio of zinc stearate in the metal magnetic ring is 0.3-0.4 wt %; the specification of the metal magnetic ring is (26-28) mm OD×(14-16) mm ID×(10-12) mm tall, and OD, ID and tall refer to the outer diameter, inner diameter and height of the metal magnetic ring respectively;
[0047] (5) The metal magnetic ring is heat-treated in a nitrogen and / or inert gas atmosphere, wherein the inert gas includes helium and / or argon, and the heat treatment temperature is 700-850° C. and the time is 30-40 min to obtain a ternary insulation-coated metal magnetic powder core.
[0048] In a second aspect, the present invention provides a ternary insulation-coated metal magnetic powder core, wherein the metal magnetic powder core is prepared by the preparation method described in the first aspect.
[0049] In a third aspect, the present invention provides an application of the metal magnetic powder core as described in the first aspect, wherein the metal magnetic powder core is used to prepare a micromotor, an inductor device or a pulse transformer.
[0050] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] (1) The present invention uses inorganic insulating powder, organic insulating agent and adhesive to insulate iron-based alloy magnetic powder of specific particle size, and then presses it into a ring, and eliminates the internal stress generated during the pressing process by heat treatment, so as to finally obtain a metal magnetic powder core with low loss, high superposition and high quality factor; wherein the insulating coating increases the resistivity of the soft magnetic composite material, thereby effectively reducing the eddy current loss between particles, and broadening the application field of the soft magnetic composite material;
[0053] (2) The preparation method provided by the present invention has a simple process flow, is easy to operate, has low cost, and has high production efficiency. Moreover, the method is green and environmentally friendly and is suitable for large-scale industrial production. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0055] Example 1
[0056] This embodiment provides a ternary insulation-coated metal magnetic powder core and a preparation method thereof, the preparation method comprising the following steps:
[0057] (1) performing particle size classification on the metal magnetic powder to obtain an Al-Si-Fe alloy magnetic powder with a medium particle size D50 of 55 μm;
[0058] (2) adding kaolin having an average particle size of 200 meshes to the sendust alloy magnetic powder, and stirring the mixture to obtain a first magnetic powder; the kaolin accounts for 2.5 wt % of the first magnetic powder;
[0059] (3) First, add silane coupling agent KH-550 to the first magnetic powder for insulation treatment, stir evenly, then add methyl silicone resin KR-251 within 5 minutes for reinforcement treatment, and dry for 2 hours to obtain the second magnetic powder; the proportion of the silane coupling agent KH-550 in the second magnetic powder is 1.5wt%, and before adding, it is diluted with 2 volumes of anhydrous ethanol and stirred for 2 minutes; the proportion of the methyl silicone resin KR-251 in the second magnetic powder is 3.5wt%, and before adding, it is diluted with 2 volumes of acetone and stirred for 2 minutes;
[0060] (4) adding zinc stearate to the second magnetic powder, grinding and mixing them uniformly, pressing them into a ring under the conditions of 25° C. and 1700 MPa to obtain a metal magnetic ring; the proportion of zinc stearate in the metal magnetic ring is 0.3 wt %; the specification of the metal magnetic ring is 26.9 mm OD×14.7 mm ID×11.2 mm tall, and OD, ID and tall refer to the outer diameter, inner diameter and height of the metal magnetic ring respectively;
[0061] (5) In order to eliminate the internal stress generated during the pressing process, the metal magnetic ring is heat treated in a nitrogen atmosphere at a temperature of 750°C for 30 min. The total heating and heat treatment time does not exceed 150 min, thereby obtaining a ternary insulation-coated metal magnetic powder core.
[0062] Example 2
[0063] This embodiment provides a ternary insulation-coated metal magnetic powder core and a preparation method thereof, the preparation method comprising the following steps:
[0064] (1) performing particle size classification on the metal magnetic powder to obtain iron-silicon alloy magnetic powder with a medium particle size D50 = 30 μm;
[0065] (2) adding kaolin with an average particle size of 500 meshes to the iron-silicon alloy magnetic powder, stirring evenly to obtain a first magnetic powder; the proportion of the kaolin in the first magnetic powder is 1.5wt%;
[0066] (3) First, add silane coupling agent KH-631 to the first magnetic powder for insulation treatment, stir evenly, then add polyester resin modified silicone KR-5235 within 5 minutes for reinforcement treatment, and dry for 2 hours to obtain the second magnetic powder; the proportion of the silane coupling agent KH-631 in the second magnetic powder is 1.0wt%, and before adding, it is diluted with 2 volumes of anhydrous ethanol and stirred for 2 minutes; the proportion of the polyester resin modified silicone KR-5235 in the second magnetic powder is 1.5wt%, and before adding, it is diluted with 2 volumes of acetone and stirred for 2 minutes;
[0067] (4) adding zinc stearate to the second magnetic powder, grinding and mixing them uniformly, pressing them into a ring under the conditions of 25° C. and 1900 MPa to obtain a metal magnetic ring; the proportion of zinc stearate in the metal magnetic ring is 0.4 wt %; the specification of the metal magnetic ring is 26.9 mm OD×14.7 mm ID×11.2 mm tall, and OD, ID and tall refer to the outer diameter, inner diameter and height of the metal magnetic ring respectively;
[0068] (5) In order to eliminate the internal stress generated during the pressing process, the metal magnetic ring is heat treated in a nitrogen atmosphere at a temperature of 770°C for 30 min. The total heating and heat treatment time does not exceed 180 min, thereby obtaining a ternary insulation-coated metal magnetic powder core.
[0069] Example 3
[0070] This embodiment provides a ternary insulation-coated metal magnetic powder core and a preparation method thereof, the preparation method comprising the following steps:
[0071] (1) performing particle size classification on the metal magnetic powder to obtain Sendust aluminum alloy magnetic powder with a medium particle size D50 = 14 μm;
[0072] (2) adding silicon dioxide with an average particle size of 1000 mesh to the sendust alloy magnetic powder, stirring evenly to obtain a first magnetic powder; the silicon dioxide accounts for 2 wt % of the first magnetic powder;
[0073] (3) First, add silane coupling agent KH-550 to the first magnetic powder for insulation treatment, stir evenly, then add methyl silicone resin KR-251 within 5 minutes for reinforcement treatment, and dry for 2 hours to obtain the second magnetic powder; the proportion of the silane coupling agent KH-550 in the second magnetic powder is 1.0wt%, and before adding, it is diluted with 2 times the volume of anhydrous ethanol and stirred for 2 minutes; the proportion of the methyl silicone resin KR-251 in the second magnetic powder is 2.5wt%, and before adding, it is diluted with 2 times the volume of acetone and stirred for 2 minutes;
[0074] (4) adding zinc stearate to the second magnetic powder, grinding and mixing them evenly, pressing them into a ring under the conditions of 25° C. and 1800 MPa to obtain a metal magnetic ring; the proportion of zinc stearate in the metal magnetic ring is 0.4 wt %; the specification of the metal magnetic ring is 26.9 mm OD×14.7 mm ID×11.2 mm tall, and OD, ID and tall refer to the outer diameter, inner diameter and height of the metal magnetic ring respectively;
[0075] (5) In order to eliminate the internal stress generated during the pressing process, the metal magnetic ring is heat treated in a nitrogen atmosphere at a temperature of 730°C for 30 min. The total heating and heat treatment time does not exceed 150 min, thereby obtaining a ternary insulation-coated metal magnetic powder core.
[0076] Example 4
[0077] The present embodiment provides a ternary insulating coated metal magnetic powder core and a preparation method thereof. In the preparation method, except that the proportion of kaolin in the first magnetic powder in step (2) is reduced to 0.3wt%, the remaining steps and conditions are the same as those in Example 1 and are not described herein.
[0078] Example 5
[0079] The present embodiment provides a ternary insulation coated metal magnetic powder core and a preparation method thereof. In the preparation method, except that the proportion of the silane coupling agent KH-550 in the second magnetic powder in step (3) is reduced to 0.3wt%, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0080] Example 6
[0081] The present embodiment provides a ternary insulating coated metal magnetic powder core and a preparation method thereof. In the preparation method, except that the proportion of methyl silicone resin KR-251 in the second magnetic powder in step (3) is reduced to 0.8wt%, the remaining steps and conditions are the same as those in Example 1 and are not described herein.
[0082] Example 7
[0083] The present embodiment provides a ternary insulation coated metal magnetic powder core and a preparation method thereof. Except that the pressure of pressing into a ring in step (4) is reduced to 1000 MPa, the remaining steps and conditions of the preparation method are the same as those of Example 1, and thus are not described in detail here.
[0084] Example 8
[0085] The present embodiment provides a ternary insulation coated metal magnetic powder core and a preparation method thereof. Except for reducing the heat treatment temperature in step (5) to 650° C., the remaining steps and conditions of the preparation method are the same as those of Example 1, and thus are not described in detail here.
[0086] Comparative Example 1
[0087] This comparative example provides a metal magnetic powder core and a preparation method thereof. Except for removing step (2), the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0088] Comparative Example 2
[0089] This comparative example provides a metal magnetic powder core and a preparation method thereof, the preparation method comprising the following steps:
[0090] (1) performing particle size classification on the metal magnetic powder to obtain an Al-Si-Fe alloy magnetic powder with a medium particle size D50 of 55 μm;
[0091] (2) adding 0.9 wt % phosphoric acid solution to the Sendust aluminum alloy magnetic powder for passivation treatment, mixing evenly and drying in a drying oven at 60° C. for 30 min to obtain a first magnetic powder;
[0092] (3) adding 6 wt % potassium silicate coating liquid to the first magnetic powder for insulation treatment, and stirring evenly to obtain a second magnetic powder;
[0093] (4) adding zinc stearate to the second magnetic powder, grinding and mixing them evenly, pressing them into a ring under the conditions of 25° C. and 1800 MPa to obtain a metal magnetic ring; the proportion of zinc stearate in the metal magnetic ring is 0.3 wt %; the specification of the metal magnetic ring is 26.9 mm OD×14.7 mm ID×11.2 mm tall, and OD, ID and tall refer to the outer diameter, inner diameter and height of the metal magnetic ring respectively;
[0094] (5) In order to eliminate the internal stress generated during the pressing process, the metal magnetic ring is heat treated in a nitrogen atmosphere at a temperature of 700°C for 30 min. The total heating and heat treatment time does not exceed 150 min to obtain a metal magnetic powder core.
[0095] The metal magnetic powder cores obtained in Examples 1-8 and Comparative Examples 1-2 were wound and tested for performance. The primary coil and the secondary coil had 20 turns each. The inductance was tested using an LCR CH3303 inductor and the magnetic permeability was converted. The total loss was tested using an AC BH meter at 50mT and 100kHz. The relevant results are shown in Table 1 below.
[0096] Table 1
[0097] Metal powder core Sensitivity(uH) Magnetic permeability(u) <![CDATA[Total loss (kW / m 3 )]]> Example 1 30.0±5% 60 136 Example 2 40.5±5% 75 466 Example 3 30.0±5% 60 86 Example 4 34.0±5% 65 130 Example 5 31.5±5% 62 145 Example 6 36.5±5% 70 210 Example 7 25.5±5% 50 184 Example 8 27.5±5% 53 290 Comparative Example 1 34.5±5% 67 135 Comparative Example 2 28.5±8% 59 214
[0098] It can be seen from Table 1 that the ternary insulating coated metal magnetic powder core provided by the present invention comprises inorganic salt oxides (such as kaolin, silicon dioxide, etc.), silane coupling agents, and silicone resins. When the three are used in combination, the process is simple, the cost is low, and the environment is green. If one of the components is changed or missing, problems such as large-scale fluctuations in inductance and increased losses will occur.
[0099] Comparison between Example 4 and Example 1: The kaolin ratio is greatly reduced, resulting in a rapid increase in inductance (magnetic permeability), and more silicone resin needs to be added to reduce the inductance to the design requirement, which in turn leads to a significant increase in cost.
[0100] Comparison between Example 5 and Example 1: The proportion of silane coupling agent KH-550 is greatly reduced, resulting in increased inductance, especially increased loss, decreased silicone insulation effect, and difficulty in molding.
[0101] Comparison between Example 6 and Example 1: A significant reduction in the proportion of silicone resin KR-251 leads to a rapid increase in inductance, a significant increase in loss, and a deterioration in core performance, indicating that silicone resin has an important influence on the insulation performance of the magnetic powder core.
[0102] Embodiments 7 and 8 respectively change the process parameters, resulting in the deterioration phenomenon of inductance being too low and loss being too high, which illustrates that the process parameters involved in the present invention play an important role and highlights the rigor of the ternary insulating material and its correct use method.
[0103] Comparative Example 1 does not use any inorganic salt oxide for adjustment, resulting in a more serious result than Example 4.
[0104] Comparative Example 2 adopts a process method of phosphoric acid passivation and potassium silicate solution adjustment. Although the process is simple, the material cost is high and not environmentally friendly. Potassium silicate causes problems such as difficulty in molding and easy cracking.
[0105] It can be seen that the present invention uses inorganic insulating powder, organic insulating agent and adhesive to insulate and coat iron-based alloy magnetic powder of specific particle size, and then presses it into a ring and eliminates the internal stress generated in the pressing process through heat treatment, so as to finally obtain a metal magnetic powder core with low loss, high superposition and high quality factor; wherein, the insulating coating increases the resistivity of the soft magnetic composite material, thereby effectively reducing the eddy current loss between particles and broadening the application field of the soft magnetic composite material.
[0106] In addition, the preparation method provided by the present invention has a simple process flow, convenient operation, low cost, high production efficiency, and the method is green and environmentally friendly and suitable for large-scale industrial production.
[0107] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a ternary insulating coated metal magnetic powder core, characterized in that: The preparation method comprises the following steps: (1) Classifying the particle size of metal magnetic powder; (2) mixing metal magnetic powder and inorganic insulating powder to obtain a first magnetic powder; (3) mixing the first magnetic powder, the organic insulating agent and the adhesive, and drying to obtain the second magnetic powder; (4) mixing the second magnetic powder and the lubricant, and pressing the mixture into a ring to obtain a metal magnetic ring; (5) heat treating the metal magnetic ring to obtain a metal magnetic powder core coated with ternary insulation; Wherein, the metal magnetic powder in step (1) includes iron silicon alloy magnetic powder and / or iron silicon aluminum alloy magnetic powder, and the particle size of the metal magnetic powder is 5-100 μm.
2. The preparation method according to claim 1, characterized in that: The particle size classification standards in step (1) include: D50=5-20 μm, D50=20-35 μm and D50=35-75 μm.
3. The preparation method according to claim 1 or 2, characterized in that: The inorganic insulating powder in step (2) comprises any one of kaolin, glass powder or silicon dioxide or a combination of at least two thereof; Preferably, the average particle size of the kaolin is 200-1000 mesh; Preferably, the average particle size of the glass powder is 200-1000 mesh; Preferably, the average particle size of the silicon dioxide is 1000-2000 mesh; Preferably, the inorganic insulating powder in step (2) accounts for 0.5-5wt% of the first magnetic powder; Preferably, the type and particle size of the inorganic insulating powder in step (2) are compatible with the particle size classification of the metal magnetic powder, specifically including: when the inorganic insulating powder is kaolin and / or glass powder with an average particle size of 200-400 mesh, the metal magnetic powder with a mixed particle size of D50=35-75μm; when the inorganic insulating powder is kaolin and / or glass powder with an average particle size of 400-1000 mesh, the metal magnetic powder with a mixed particle size of D50=20-35μm; when the inorganic insulating powder is silica with an average particle size of 1000-2000 mesh, the metal magnetic powder with a mixed particle size of D50=5-20μm.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mixing method in step (3) includes: firstly adding an organic insulating agent to the first magnetic powder for insulation treatment, stirring evenly, and then adding an adhesive for reinforcement treatment; Preferably, the organic insulating agent comprises silane, and the type of the silane comprises any one of KH-550, KH-621, KH-631, DL-602 or DL-171 or a combination of at least two thereof; Preferably, the proportion of the organic insulating agent in the second magnetic powder is 0.5-1.5wt%; Preferably, the adhesive comprises a silicone resin, and the type of the silicone resin comprises any one of methyl silicone resin KR-251, polyester resin modified silicone KR-5235, alkyl silicone resin JM10 or methyl phenyl silicone resin REN60, or a combination of at least two thereof; Preferably, the proportion of the adhesive in the second magnetic powder is 1.0-5.5wt%.
5. The preparation method according to claim 4, characterized in that: The organic insulating agent and the adhesive are diluted separately before being added; Preferably, the organic insulating agent uses anhydrous ethanol as a diluent, and the volume ratio of the diluent to the organic insulating agent is (1.5-2.5):1; Preferably, the adhesive uses acetone as a diluent, and the volume ratio of the diluent to the adhesive is (1.5-2.5):
1.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The lubricant in step (4) comprises zinc stearate, and the proportion of the lubricant in the metal magnetic ring is 0.3-0.4wt%; Preferably, the temperature of pressing into rings in step (4) is 20-30°C; Preferably, the pressure for pressing into a ring in step (4) is 1500-2500 MPa; Preferably, the specifications of the metal magnetic ring in step (4) are (26-28) mm OD×(14-16) mm ID×(10-12) mm tall, and OD, ID and tall respectively refer to the outer diameter, inner diameter and height of the metal magnetic ring.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The heat treatment in step (5) is performed in a nitrogen and / or inert gas atmosphere, wherein the inert gas includes helium and / or argon; Preferably, the temperature of the heat treatment in step (5) is 700-850°C; Preferably, the heat treatment time in step (5) is 30-40 minutes.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) performing particle size classification on metal magnetic powder with a particle size of 5-100 μm, wherein the particle size classification standards include: D50=5-20 μm, D50=20-35 μm and D50=35-75 μm, and the metal magnetic powder includes iron silicon alloy magnetic powder and / or iron silicon aluminum alloy magnetic powder; (2) mixing metal magnetic powder and inorganic insulating powder to obtain a first magnetic powder; the inorganic insulating powder comprises any one of kaolin, glass powder or silicon dioxide or a combination of at least two thereof, and the average particle size of the kaolin and glass powder is independently 200-1000 mesh, and the average particle size of the silicon dioxide is 1000-2000 mesh; the proportion of the inorganic insulating powder in the first magnetic powder is 0.5-5wt%, and the type and particle size of the inorganic insulating powder are suitable for the particle size classification of the metal magnetic powder. The method comprises: when the inorganic insulating powder is kaolin and / or glass powder with an average particle size of 200-400 mesh, the metal magnetic powder with a particle size of D50=35-75 μm is mixed; when the inorganic insulating powder is kaolin and / or glass powder with an average particle size of 400-1000 mesh, the metal magnetic powder with a particle size of D50=20-35 μm is mixed; when the inorganic insulating powder is silicon dioxide with an average particle size of 1000-2000 mesh, the metal magnetic powder with a particle size of D50=5-20 μm is mixed; (3) firstly adding an organic insulating agent to the first magnetic powder for insulation treatment, stirring evenly, then adding an adhesive for reinforcement treatment, and drying to obtain a second magnetic powder; the organic insulating agent comprises silane, which accounts for 0.5-1.5wt% of the second magnetic powder, and the type of the silane comprises any one of KH-550, KH-621, KH-631, DL-602 or DL-171 or a combination of at least two; the adhesive comprises an organic silicone resin, which accounts for 1.0-5.5wt% of the second magnetic powder, and the organic silicone resin comprises an organic silicone resin. The type of resin includes any one of methyl silicone resin KR-251, polyester resin modified silicone KR-5235, alkyl silicone resin JM10 or methyl phenyl silicone resin REN60, or a combination of at least two thereof; the organic insulating agent and the adhesive are independently diluted before being added, and the organic insulating agent uses anhydrous ethanol as a diluent, and the volume ratio of anhydrous ethanol to the organic insulating agent is (1.5-2.5):1; the adhesive uses acetone as a diluent, and the volume ratio of acetone to the adhesive is (1.5-2.5):1; (4) mixing the second magnetic powder and zinc stearate, pressing into a ring at 20-30° C. and 1500-2500 MPa to obtain a metal magnetic ring; the ratio of zinc stearate in the metal magnetic ring is 0.3-0.4 wt %; the specification of the metal magnetic ring is (26-28) mm OD×(14-16) mm ID×(10-12) mm tall, and OD, ID and tall refer to the outer diameter, inner diameter and height of the metal magnetic ring respectively; (5) The metal magnetic ring is heat-treated in a nitrogen and / or inert gas atmosphere, wherein the inert gas includes helium and / or argon, and the heat treatment temperature is 700-850° C. and the time is 30-40 min to obtain a ternary insulation-coated metal magnetic powder core.
9. A three-element insulation-coated metal magnetic powder core, characterized in that: The metal magnetic powder core is prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the metal magnetic powder core as claimed in claim 9, characterized in that: The metal magnetic powder core is used for preparing micro motors, inductance devices or pulse transformers.
